2020
DOI: 10.13189/saj.2020.080101
|View full text |Cite
|
Sign up to set email alerts
|

Sports Activities for Undergraduate Students in Saudi Arabia Universities: A Systematic Literature Review

Abstract: Objectives: Kingdom of Saudi Arabia (KSA) has experienced tremendous economic growth in the past few years and this in turn has led to undesirable lifestyle behaviors coupled with an associated rise in non-communicable diseases. This has forced the KSA administration to encourage sports related activities for a healthy life style. In this article, a Systematic Literature Review (SLR) is presented to discuss the current state of Physical Activity (PA) and sports activities in KSA and Other Countries in the Worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Schools should provide sports facilities and programs suitable for students. The availability of sports facilities and projects has a great impact on college students' sports participation (Sayyd et al, 2021). The sports facilities provided by the school can actively encourage students to use these facilities and participate in sports activities.…”
Section: Sports Facilitiesmentioning
confidence: 99%
“…Schools should provide sports facilities and programs suitable for students. The availability of sports facilities and projects has a great impact on college students' sports participation (Sayyd et al, 2021). The sports facilities provided by the school can actively encourage students to use these facilities and participate in sports activities.…”
Section: Sports Facilitiesmentioning
confidence: 99%
“…Because of this, these studies have demonstrated that university sports facilities, regardless of gender, have a good effect on students' involvement. 21,25,26 Copyright: ©2023 Sayyd et…”
Section: Facilitiesmentioning
confidence: 99%
“…Sayyds et al study revealed that the most important factors that impede the success of physical and sports activities among males in the universities of the Kingdom of Saudi Arabia are a lack of energy, motivation, self-confidence, and time, while females face a lack of social support and resources [14]. This highlights the need for more research to realize the potential in this field in the Kingdom of Saudi Arabia and achieve the goals of Vision 2030.…”
Section: Introductionmentioning
confidence: 99%